Eco-design of Low Energy Mechanical Milling Through Implementation of Quality Function Deployment and Design for Sustainability - Muhammad Hanif, Abd Rashid; Nik Hisyamudin, Muhd Nor; Siti Norhana, Selamat; Mohd Fahrul, Hassan; Abd Khalil, Abd Rahim; Mohd Fauzi, Ahmad; Al Emran, Ismail; Badrul, Omar; Mohd Faiz, Mokhtar; Faiz, Mohd Turan; Yokoyama, Seiji (AIP Publishing, 2017)
Malaysia as a developing country favor energy demand by years which created mainly from fossil fuel. Unfortunately, the action leads to significant increment in carbon dioxide (CO2) emission that causing the global warming. The most promising mitigation strategy is by deploying Carbon Capture and Storage (CCS) technology where mineral carbonation was identified as the safest method for permanent storage and does not require continuous monitoring. Accordingly, National Green Technology was launched in 2009 to support the growth of green technology development in Malaysia as a carbon mitigation strategy. Thus, this paper aims to propose the development of a conceptual eco-design for Low Energy Mechanical Milling (LEMM). The concept was proposed by using the Quality Function Deployment (QFD) tool with combination of sustainability determinants (DFS) namely economic, environmental and social which evaluated using Solidworks 2015 sustainability assessment. The results show the new product targets for LEMM in prior on energy consumption (MJ), selling price (MYR), material cost (MYR), carbon footprint (kg CO2) with weightage of 5.2, 4.2, 3.6 and 3.6 respectively. The implementation of DFS criteria into the QFD promote to reduce material used by 16%, 35% reduction of carbon footprint, 28% less energy consumption, 28% lower air acidification, 77% of water eutrophication declined and increased recyclability by 15%.